Corporate Governance, Tax Avoidance and Accrual-Based Earnings Management on Firm Value: an Interactive Effect in Indonesia’s Perspective - Mappadang, Agoestina; Indrabudiman, Amir; Melansinaga, Melansinaga (Opción, 2019)
Purpose:In this study, we examine the link between corporate governance mechanism and firm value and identify the mediation effect of tax avoidance- and earnings management.This study investigated how tax avoidance meas- ured by avoidance tax rate (ATR) and earnings management measured by dis- cretionary accrual as a basis of management affects the firm value. Design/ Research method: We useda sampleassociated with manufacturing industry listed in Indonesia Stock Exchange from 2013 to 2017. The sample was de- termined by the purposive sampling method and contains395 objects of unit analysis from 79 companies.This research worked on secondary data witha- nalysis of causality. The analysis used Partial Least Square method with the assistance of Smart PLS3 software. Finding:The results show that the cor- porate governance mechanism has a negative and significant impact on tax avoidance and earnings management. Meanwhile, the corporate governance mechanism has a positive and significant impact on the firm value.Thecorpo- rate governance on the firm value with tax avoidance as mediate variable has a negative and significant impact, besides earnings management as mediate variable has a positive and significant impact. Limitation:Measurement of tax avoidance by ATR only be used on a sample of manufacturing industries in this study period. It should test measurements on different industries in extended research period.The corporate governance only used mechanism of corporate governance for future research should focus on analyzing compos- ite governance scores. Implication:The implications of this study on the concept of agency theory in corporate governance that management is able to provide confidence to investors that the funds are invested safely and get return.Secondly, im- plications of losses to be borne by various parties in the long term if the company still practices tax avoidance and earnings management.